Estudo farmacognóstico e atividades biológicas de Polygala boliviensis A.W. Benn - Silva, Danielle Figuerêdo da (2020)
Studies corroborate the popular use of species of the genus Polygala, however Polygala boliviensis A.W. Benn (Polygalaceae), found in the semi-arid region of Bahia, has few chemical and pharmacological studies. Thus, this work aimed to conduct a pharmacognostic study and the biological activities of P. boliviensis. The collection of the aerial parts and roots of the species, for the different stages, was performed at the UEFS campus, in Feira de Santana, Bahia. For the isolation of secondary metabolites, methanolic extract was prepared by maceration, followed by partition with hexane, chloroform and ethyl acetate, and successive procedures by column chromatography. The identification of the isolated metabolites was performed by one- and two-dimensional NMR, resulting in the chemical structures of 1,3,5-trihydroxy-2-methoxyxanthone, α-spinasterol, as well as a coumarin and fatty acid mixture that are in confirmation phase. In the evaluation of biological activity, the coumarins auraptene and polygalen, previously isolated from P. boliviensis, were evaluated by MTT test and in vitro antiplasmodial activity against chloroquine-resistant strain of Plasmodium falciparum (W2), and showed IC50 = 13.46 ± 0.03 μM and EC50 = 0.171 ± 0.016 for auraptene; and above 100 μM and 0.164 ± 0.012 for poligalen, resulting in the selectivity index of 78.71 and 609.76, respectively. These coumarins were also subjected to docking-based inverse virtual screening using P. falciparum targets from BraMMT, demonstrating better affinity to purine nulceoside phosphorylase and dihydroorotate dehydrogenase enzymes. We also evaluated the seasonal variation of the chemical composition through the identification and quantification of secondary metabolites by HPLC-DAD; the antioxidant activity, through the DPPH-free radical scavenging test and inhibition of β-carotene auto-oxidation; and the lethality against Artemia salina. By this method, gallic acid, rutin, poligalen, auraptene, and 7 unknown major peaks were identified, which through UV spectra, are believed to be phenolic acids, flavonoids, xanthones, coumarins, and styrylpyrones. Although there was no seasonal variation in the yield of extracts and chemical profile, there was quantitative variation of metabolites, antioxidant activity and lethality against A. salina. For the anatomical characterization light microscopy was used, analyzing samples included in historesin and stained with toluidine blue, while for histochemistry, the samples were sectioned in cryomicrotome and submitted to different tests. P. boliviensis showed amphistomatic leaves and non-glandular trichomes on the leaves and stems, in addition to lysigenous secretory cavities found in the leaves and responsible for lipid secretion. This study contributes to the chemical characterization of P. boliviensis, as well as to taxonomic delimitations, facilitating the differentiation between morphologically similar species, and corroborating the chemosystematics of the genus Polygala. Added to this, the diversity of the chemical composition and antiplasmodial activity demonstrated by auraptene and poligalen reinforce the phytotherapeutic potential of the species, but as seasonality influences the amount of these and other secondary metabolites, it should be considered, facilitating the determination of the collection period or ideal cultivation conditions, to obtain the metabolites of interest.